Implementation of CMOS-compatible Metamaterial Absorber for gas Sensing Application. (2016) - Shahmarvandi, E. Karimi; Ghaderi, M.; Ayerden, P.; de Graaf, G.; Wolffenbuttel, R.F.
Abstract: The design of a metamaterial-based absorber for use in a mid-IR microspectrometer-based gas sensor is reported. The microspectrometer consists of a linear variable optical filter (LVOF) that is aligned with an array of thermopile detectors, which is fabricated on a SiN membrane and covered with the absorber. Special emphasis was put on the CMOS compatible fabrication, which resulted in an absorber design based on aluminium disk resonators and an aluminium background plane that are separated by a SiO2 layer. The fabrication process is described, and the challenges are discussed.